2010
DOI: 10.1128/jvi.02732-09
|View full text |Cite
|
Sign up to set email alerts
|

Infection by Discordant Strains of HIV-1 Markedly Enhances the Neutralizing Antibody Response against Heterologous Virus

Abstract: High-risk cohorts in East Africa and the United States show rates of dual HIV-1 infection-the concomitant or sequential infection by two HIV-1 strains-of 50% to 100% of those of primary infection, and our normalrisk HIV-positive cohort in Cameroon exhibits a rate of dual infection of 11% per year, signifying that these infections are not exceptional. Little is known regarding the effect of dual infections on host immunity, despite the fact that they provide unique opportunities to investigate how the immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 31 publications
4
49
1
Order By: Relevance
“…Another factor that has been implicated in the development of breadth is HIV-1 sequence diversity, with individuals with greater envelope diversity early in infection developing greater breadth during chronic infection (30). This observation is supported by recent data showing that dual infection results in broader and more potent nAb responses (31). CAP256 was superinfected in the window between the initial infection and the development of autologous nAb responses, and recombination between the two infecting strains resulted in substantial viral variation over the first year of infection (data not shown).…”
Section: Discussionmentioning
confidence: 77%
“…Another factor that has been implicated in the development of breadth is HIV-1 sequence diversity, with individuals with greater envelope diversity early in infection developing greater breadth during chronic infection (30). This observation is supported by recent data showing that dual infection results in broader and more potent nAb responses (31). CAP256 was superinfected in the window between the initial infection and the development of autologous nAb responses, and recombination between the two infecting strains resulted in substantial viral variation over the first year of infection (data not shown).…”
Section: Discussionmentioning
confidence: 77%
“…Two recent studies have shown that superinfection resulted in greater neutralizing breadth and potency (46,47). In one of these studies, broad and potent NAb responses developed in 2 elite neutralizers very soon after infection with a second virus, suggesting that the development of breadth was accelerated through superinfection (46).…”
Section: Discussionmentioning
confidence: 99%
“…Whether a similar situation provoked the exceptional breadth in CAP256 is unknown. It is possible that superinfection with a discordant virus results in the broadening of the NAb response to multiple epitopes presented on discordant viruses (48), a model supported by the fact that greatest breadth was associated with intersubtype superinfection (46,47). It is also possible that superinfection focuses the NAb response onto conserved epitopes common to both infecting viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence, though inconclusive, is not encouraging. The incidence of superinfection varies from 50% to 100% of the primary-infection rate in uninfected control cohorts, [22][23][24] and superinfection occurs in the face of substantial crossneutralizing titers, also specifically against early posttransmission forms of the virus. 22 However, the minority of subjects with broad and strong NAb responses may be too small to make a detectable impact, and the NAb titers may even more rarely reach the high levels found experimentally to be required for protection.…”
mentioning
confidence: 99%